Critical Analysis of the Child's Best Interest Principle in Lamongan's 2025 Juvenile Criminal Verdicts - Hidayah, Nur; Putri, Nabilla Desyalika (Sekolah Tinggi Ilmu Kepolisian, 2026)
This study emphasizes the importance of applying the child's best interest principle within the juvenile criminal justice system, a core concept recognized both internationally and nationally. This principle views children as legal entities entitled to protection, focusing on guidance, rehabilitation, and their prospects. Although Indonesia has incorporated this principle into many regulations, especially Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, there remains a gap between legislative provisions and practical enforcement. This is evident in the continued use of a repressive approach in juvenile court rulings, such as at Lamongan District Court in 2025. This study employs a normative legal research method, using both a statutory approach and a case study approach. The data includes primary legal sources like legislation and six juvenile case rulings from Lamongan District Court in 2025. Secondary sources, such as scholarly books and journals, are also used. The analysis follows a descriptive-qualitative method to evaluate how closely judicial practices follow the legal principles of the child's best interests. The findings reveal that the application of the child's best interest principle in these rulings has been inconsistent and suboptimal. Despite efforts to combine criminal sanctions with vocational training, rulings mostly remain repressive. Diversion processes have not been fully implemented, even when cases meet the criteria. Moreover, the recommendations from the Correctional Institution's reports have not been fully integrated into decision-making. This indicates that a restorative approach is still weakly practiced, and there is a gap between legal norms and judicial procedures. Therefore, it is essential to strengthen institutions, enhance the capacity of law enforcement officers, and promote a shift towards a more rehabilitative, child-centred approach.